Bio-Nanohybrid Cell Based Signal Amplification System for Electrochemical Sensing - Wang, Jing-Xian; Yang, Xue-Jin; Wang, Yan-Zhai; Yang, Kai; Chen, Huayou; Yong, Yang-Chun (Analytical chemistry (Washington), 2022)
A signal amplification system for electrochemical sensing was established by bio-nanohybrid cells (BNC) based on bacterial self-assembly and biomineralization. The BNC was constructed by partially encapsulating a Shewanella oneidensis MR-1 cell with the self-biomineralized iron sulfide nanoparticles. The iron sulfide nanoparticle encapsulated BNCs showed high transmembrane electron transfer efficiency and was explored as a superior redox cycling module. Impressively, by integrating this BNC redox cycling module into the electrochemical sensing system, the output signal was amplified over 260 times compared to that without the BNC module. Uniquely, with this BNC redox cycling system, ultrasensitive detection of riboflavin with an extremely low LOD of 0.2 nM was achieved. This work demonstrated the power of BNC in the area of biosensing and provided a new possibility for the design of a whole cell redox cycling based signal amplification system.